Manufacturing automation technology development : selected, peer reviewed papers from the 14th Conference of China University Society on Manufacturing Automation, August 11-14, 2010, Jiaozuo, China - Zhao, Bo (Key engineering materials ;, 2010)
The major topics covered by these 139 peer reviewed papers include: Innovation and Experience in Manufacturing Automation Education, Situation and Development Summarization on Manufacturing Automation, Advanced Manufacturing Technology, and Administrative Skill of Advanced Manufacturing.